Family and population changes in Singapore a unique case in the global family change - Yeung, Wei-Jun Jean 1958-; Hu, Shu (Routledge, 2018)
"This book depicts the evolution of Singapore's family and population landscape in the last half a century, the related public policies, and future challenges. Since the country's independent in 1965, family and population policies have been an integral part of its national building developmental strategies. The chapters discuss the changes in population compositions, family structures, relations, values among major ethnic groups. They also discuss policies for vulnerable populations such as female-headed households, cross-cultural families, same-sex partnering, the elderly, and low-income families. In the context of global family changes, Singapore's experience is by no means a linear extrapolation of those in the western industrialized countries, but a unique case in the global family change."--Provided by publisher
Keywords: Families / Singapore